Could football be a valid tool to combat adolescents' physical inactivity? A Descriptive Study - Jose Coto-Lousas; Javier Fernandez-Rio (Asociación Española de Ciencias del Deporte, 2024)
Football is considered the most popular sport among adolescents, but most do not meet the World Health Organization's recommendation of 60 minutes of moderate to vigorous physical activity (MVPA) per day. Can regular football practice help to meet this recommendation? This research aimed to assess the physical activity levels of players in a high-performance football academy, both in training and in matches, using accelerometry. In addition, the study aimed to analyze the coaching style of the participants' coaches using the researcher's diary. A total of 130 players from a Spanish professional La Liga team agreed to participate: Under 18 (U18), Under 15 (U15) and Under 13 (U13). In addition, the subjective perception of total quality of recovery (TQR) and perceived exertion (RPE) before and after each training session/match, as well as their coaches, were analysed. The results showed that the average minutes of MVPA per training session and match with more than 60 minutes played were respectively: U18: 61.46 ± 2.45 and 77.78 ± 5.93, U15: 50.84 ± 3.78 and 79.63 ± 14.84, and U13: 53.35 ± 4.96 and 74.04 ± 14.73. Players were consistently considered "very well recovered" (TQR). The RPE values of coaches and players were similar during training, but higher for coaches in competition. The U18 coaches showed a coaching style of autonomy support, while the U15 and U13 categories showed a controlling style. In conclusion, weekly football practice in a high-performance academy may enable adolescent players to meet international MVPA recommendations for health benefits by encouraging an active lifestyle.